Pembuatan Arang Aktif Dari Cangkang Pala (Myristica Fragrans Houut) Dan Aplikasinya Untuk Penjernihan Asap Cair Serta Analisis FTIR. - Gomes, Esri; Lombok, John; Caroles, Joice (Jurnal Kimia Fullerene, 2024)
Research on activated charcoal from nutmeg shells (Myristica Fragrans Houut) and its application for liquid smoke clarification and FTIR analysis has been carried out. This study aims to determine the functional groups and composition of nutmeg shell charcoal from Siau Island. This research includes pyrolysis stage, charcoal activation stage and functional group analysis with Fourier Transform Infra-Red (FTIR). The FTIR test results of pyrolyzed nutmeg shell charcoal and the results of activation with , and show the functional groups O-H, C-H Aromatic, C-H Aliphatic, C=C, and C-O which are the composition of the carbon material of nutmeg shell charcoal. The results of testing the physical and chemical properties of nutmeg shell charcoal, namely nutmeg shell charcoal resulting from activation with namely Moisture Content 0.533%, Ash Content 0.653%, Volatile matter content 0.406%, Bonded carbon content 40.70%. The test results for the physical properties of nutmeg shell charcoal activated with were 0.483 water content, 0.4% ash content, 0.403% volatile matter content, and 41.13% bound carbon content. The results of purifying liquid smoke with activated carbon produce reduced turbid water color, reduced smoke odor and a Ph value of 5, while liquid smoke clarification without activated carbon produces cloudy/brownish water color, pungent smoke odor and a pH value of 4.